Electronic Word-Of-Mouth (eWOM) Behavior in Malaysia: Successful Marketing Strategy - NH Marmaya; Bamini KPD Balakrishnan; ASM Shuaib (Human Resource Management Academic Research Society (HRMARS), 2018)
The major purpose of this research is to discover the influences of Active User of Social Media (AUSM), Innovativeness and Trust towards electronic word of mouth (eWOM) behaviour in Malaysia. Enormous past research on the electronic word-of-mouth, but only few have analysed the topic from Malaysian perspective. A quantitative method was adopted in this study and responses from 120 respondents in Malaysia that were analyzed using PLS-SEM. The result shows that there are significant relationship between active user of social media (AUSM), innovativeness and trust toward eWOM behaviour among Malaysian. Practically, the result indicate that electronic word of mouth behaviour via social media and mobile technology can be part of marketing strategy in promotion to influence buyer to increase sales of product of a company. This empirical study attempts to enrich the understanding of electronic word of mouth behaviour via social media and mobile technology in Malaysian context.